Oral Antibiotic in Acne Vulgaris Patients: Retrospective Study - Marina Rimadhani; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Antibiotic resistance is one of the health problem in Indonesia, the one of the reason is using combination of antibiotic, so that clinician should prevent resistance to any selected combination antibiotic therapy. The use of long period oral antibiotics in acne therapy can cause Propionibacterium acne resistanceto antibioticsincreasedfrom 20% in 1979to67% in 1996. Purpose: To describe and evaluate management of oral antibiotic in new patient with acne vulgaris. Methods: Retrospective study in patients with acne vulgaris who received oral antibiotic in Cosmetic Division Dermato-Venereology Department Outpatient Clinic of Dr. Soetomo General Hospital in period of January 2010 to December 2012. Results: Obtained 481 new patients receive oral antibiotic from the total visit of 3519 acne vulgaris patient. The proportion of the largest group of 15-24 years, female patient were found having higher incidence than male. The most clinical feature found was grade 2 papulopustular (49.6%). The most common treatment which were given to the patient were doxycycline (98.8%) for systemic treatment with topical combination therapy as sunscreen (24.8%), facial cleansers(23.6%), tretinoin(20.99%), clindamycin gel (19.3%), and benzoylperoxide(5.4%). Highest proportion of long duration use of antibiotics is 2 weeks(57.5%). Conclusions: Selection of combination therapy is appropriate, but the use oftopical antibioticsalong withoral antibioticsshould be considered. Combination therapy, duration, and education still play an important role in preventing resistance Propionibacterium acne to antibiotics.Key words: acne vulgaris, antibiotic resistance, combination therapy, retrospective.